Cost-Sharing and Out-of-Pocket Cost for Women Who Received MRI for Breast Cancer Screening. (28th July 2021) - Pan, I-Wen; Oeffinger, Kevin C; Shih, Ya-Chen Tina
Abstract: Background: The financial protection of the prevention provision of the Affordable Care Act (ACA) doesn't apply to breast MRI but only to mammography for breast cancer screening. The purpose of the study is to examine the financial burden among women who received breast magnetic resonance imaging (MRI) for screening. Methods: This observational study used the Marketscan database. Women who underwent breast MRI between 2009 and 2017 and had screening mammography within 6 months of the MRI were included. We compared the time trend of the proportion of zero cost-share for women undergoing screening mammography and that for MRI. We quantified out-of-pocket (OOP) costs as the sum of copayment, coinsurance, and deductible and defined zero cost-share as having no OOP cost. We conducted multivariable logistic regression and 2-part model to examine factors associated with zero cost-share and OOP costs of MRI, respectively. Results: During the study period, 16 341 women had a screening breast MRI. The proportion of screening MRI claims with zero cost-share decreased from 43.1% (2009) to 26.2% (2017). The adjusted mean OOP cost for women in high-deductible plans was more than twice the cost for their counterparts (549 vs 251; 2-sided P < .001). Women who resided in the South in the post–Affordable Care Act era were less likely to have zero cost-share and paid higher OOP costs for screening MRI. Conclusions: Many women are subject to high financial burden when receiving MRI for breast cancer screening. Those enrolled in high-deductible plans and who reside in the South are especially vulnerable financially.